1995
DOI: 10.1007/bf01782979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clodronate on established collagen-induced arthritis in rats

Abstract: The collagen-induced arthritis model in rats was used to study the effect of disodium clodronate on inflammation and destruction of tarsal, metatarsal, and interphalangeal bones and joints. Female DA rats were immunized with heterologous type II collagen. Fourteen days after immunization, rats with similar scores were assigned to the different experimental groups. They were treated subcutaneously either with saline (controls) or with clodronate at doses of 12.5 and 25 mg/kg/day five times a week for 2 weeks. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Bisphosphonates have been reported to reduce cartilage degradation in collagen-induced arthritis and adjuvant-induced arthritis (45)(46)(47). Recently, zoledronate was reported to be partially chondroprotective in carrageenan-induced inflammatory arthritis (48) and chymopapain-induced cartilage damage in rabbits (28).…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates have been reported to reduce cartilage degradation in collagen-induced arthritis and adjuvant-induced arthritis (45)(46)(47). Recently, zoledronate was reported to be partially chondroprotective in carrageenan-induced inflammatory arthritis (48) and chymopapain-induced cartilage damage in rabbits (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of bisphosphonate studies in experimental arthritis, the suppressive effect of single doses of ZA on focal bone destruction is noteworthy. The earlier-generation bisphosphonates usually reduced markers of increased bone resorption and physiologic bone resorption at the growth plate, although evidence of inhibition of focal bone erosions was not compelling (37)(38)(39)(40)(41)(42). A notable exception was pamidronate, which reduced the size of radiographic bone erosions in spontaneously arthritic TNF␣-transgenic mice to an extent similar to that observed with the TNF inhibitor infliximab (12).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their success in preventing systemic bone loss, however, trials with bisphosphonates in patients with RA have not demonstrated efficacy with respect to attenuating the progression of focal bone erosions (6)(7)(8)(9)(10). In contrast, results of studies in several different animal models of inflammatory arthritis indicate that bisphosphonate treatment can produce beneficial effects in both systemic bone loss and progression of focal bone erosions (3,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%